2000
DOI: 10.1159/000012381
|View full text |Cite
|
Sign up to set email alerts
|

Polysymptomatic Conversion Disorder in Childhood and Adolescence in Japan

Abstract: Background: In conversion disorder in childhood and adolescence, polysymptomatic (PS) presentations are reportedly commoner than monosymptomatic (MS) ones. Somatization disorder is also associated with pseudoneurological symptoms, but is extremely rare in childhood. This occurs despite the age of onset peaking in the teens among adult somatization disorder patients. Method: We reviewed the records of 44 children and adolescents with pseudoneurological symptoms. They were categorized as MS cases (19) or PS case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Motor symptoms are a common complaint in most other studies (Chand et al, 2000;Deka et al, 2007;Deveci et al, 2007;Ercan et al, 2003;Kuloglu et al, 2003;Sar et al, 2004). Pure sensory disturbances are relatively less common and broadly comparable across studies, albeit with some exceptions (Murase et al, 2000;Tezcan et al, 2003).…”
Section: What Is the Cross-cultural Validity Of Existing Conversion Dmentioning
confidence: 91%
See 3 more Smart Citations
“…Motor symptoms are a common complaint in most other studies (Chand et al, 2000;Deka et al, 2007;Deveci et al, 2007;Ercan et al, 2003;Kuloglu et al, 2003;Sar et al, 2004). Pure sensory disturbances are relatively less common and broadly comparable across studies, albeit with some exceptions (Murase et al, 2000;Tezcan et al, 2003).…”
Section: What Is the Cross-cultural Validity Of Existing Conversion Dmentioning
confidence: 91%
“…A similar retrospective study of 921 children (9-17 yrs.) seen in a Japanese psychiatry outpatient clinic in Japan found that 4.7% had received a diagnosis of conversion disorder recorded in their notes (Murase, Sugiyama, Ishii, Wakako, & Ohta, 2000). In the absence of prospective assessment using DSM-IV-TR criteria, however, it is impossible to know whether the figures cited by Chand and colleagues (2000) and Murase and colleagues (2000) provide an accurate estimate of prevalence according to that taxonomy.…”
Section: What Is the Evidence For Variation In Prevalence Rates Of Comentioning
confidence: 99%
See 2 more Smart Citations
“…Los autores concluyen que la mayor expresión femenina podría entenderse desde un contexto sociocultural de inhibición y represión. Por otro lado, en 18,3% de los portadores de TC se identificó un estresor agudo participante 5 , en cambio, Murase et al 46 pesquisaron 32% de eventos estresantes gatillantes. En otra prospección en niños con TS, Bujoreanu et al corroboraron que la mayoría fueron mujeres, los principales motivos de consulta dolor y fenómenos conversivos (CPNE, alteraciones sensorio-motoras, mareo) y las comorbilidades, desórdenes ansiosos y afectivos.…”
Section: Tipos Presentacionalesunclassified